A taxonomic review of the fish parasitic isopod family Cymothoidae Leach, 1818 (Crustacea: Isopoda: Cymothooidea) of India - Ravichandran, S.; Vigneshwaran, P.; Rameshkumar, G. (Zootaxa, 2019)
The parasitic isopod family Cymothoidae Leach, 1818 of the India exclusive economic zone is reviewed. A total of 56 nominal species corresponding to 48 valid species belonging to sixteen genera are reviewed from 73 host species belonging to 35 families. Mothocya plagulophora (Haller, 1880), Nerocila depressa Milne Edwards, 1840, Nerocila loveni Bovallius, 1887, Nerocila trichiura (Miers, 1877), Norileca triangulata (Richardson, 1910) and Ryukyua globosa Williams & Bunkley-Williams, 1994 are redescribed. Indusa pustulosa Pillai, 1954 is synonymised with Agarna malayi Tiwari, 1952; Cymothoa krishnai Jayadev Babu & Sanjeeva Raj, 1984 is synonymised with Cymothoa eremita (Brünnich, 1783) and Nerocila priacanthusi Kumari, Rao & Shyamasundari, 1987 is synonymised with Nerocila arres Bowman & Tareen, 1983. Ourozeuktes bopyroides (Lesueur, 1814) is revised and excluded from the Indian fauna. The Indian cymothoid species Agarna bengalensis Kumari, Rao & Shaymasundari, 1990, Cymothoa asymmetrica Pillai, 1954 and Nerocila hemirhamphusi Shyamasundari, Rao & Kumari, 1990 are regarded here as species inquirenda. A key to the Indian genera of the family Cymothoidae and keys to the Indian species of the genera Cymothoa, Joryma, Mothocya, and Nerocila are presented. A checklist of the valid Cymothoidae species until now reported from Indian marine fishes are compiled. Host preferences, morphological variability and distribution are discussed.